Woof - Ahlberg, Allan; Wegner, Fritz (New York : Puffin, 1988)
One ordinary summer evening ten-year-old Eric Banks turns into a Norfolk terrier. Eric and his best friend attempt to puzzle out the reason for his transformation.
5.0
3-6
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Humorous stories; Dogs -- Fiction; Humorous fiction